(untitled) (Jurnal Pustaka, 2025)
This research is entitled ’Jidougyakutai Actions in the Film Himizu by Sono Sion’. This research aims to identify the forms of child abuse depicted in the film "Himizu" by Sono Sion. The method used in this research is descriptive analysis. The study employs literary psychology theory by Minderop (2010), DSM-V (Child Abuse) theory by the American Psychiatric Association (APA), and semiotics theory by Marcel Danesi. Based on the research findings, the acts of child abuse reflected in Sono Sion’s "Himizu" are illustrated through the characters Yuichi Sumida and Chazawa Keiko. The types of child abuse experienced by these characters are (1) child physical abuse, (2) child neglect, and (3) child psychological abuse. Among these forms of abuse, child psychological abuse is the most dominant experienced by both characters. Child psychological abuse refers to causing emotional suffering in a child through words, actions, or neglect.